The Impact of the Internal Space Elements on the Performance of Efficiency in the Inpatient Ward - Hmoud, Saad Mohsin (Iraqi Journal of Architecture and Planning, 2017)
The health sector in Iraq is suffering from the absence of keep up with modern trends. At the healing architecture fields which is linked to Building performance of efficiency especially on interior design. That is have physical and psychological effect and impact of the users experience and mechanism of transforming this experience into realty by using elements of internal spaces. Research is based on the perception that is building performance efficiency depend on internal space elements, through patients experience on the surrounding environment in the inpatient wards. Therefore, research problem is cognitive deficiencies on the impact of internal space elements on the inpatient ward performance of efficiency. The research aim is detection the related concepts on the performance of efficiency through Internal space elements. Research methodology has represented a number of steps: first define the conceptual framework of each of the internal space elements. Moreover, the performance of efficiency in the inpatient wards. Second, build the theoretical framework for research and testing the research hypothesis by adapting The Qualitative Heuristic Approach "QHA" by using a questionnaire was built according to the theoretical framework of the concepts of satisfaction patient (acceptability) and Safety, and then analyze the results of the questionnaire using statistical software (SPSS) and then analyze the results and determine conclusions. The research conclusions show the internal space elements have the greatest impact for rising the inpatient wards performance of efficiency through rising feelings of the acceptability at all levels by providing a personal needs and privacy, equality in health services and supporter services. In addition, research found that is feeling safety on physical and psychological level achieved by specific elements in internal spaces.